Agreement between two cephalometric analyses of facial growth direction and biotype = Concordancia entre dos análisis cefalométricos de dirección de crecimiento y biotipo facial - Aguilar Pérez, Fernando Javier
Cephalometry is a morphological and descriptive diagnostic method that provides relevant data on skeletal and dentoalveolar malocclusions of patients seeking orthodontics treatment. Several authors have proposed different cephalometric measurements to determine facial growth direction and facial biotype, the results of these different measurements from the same patient do not always agree on the diagnosis. The aim of this study was to determine the level of agreement between Ricketts and Björk-Jarabak cephalometric analyses for the determination of facial growth direction and facial biotype in patients from a population of Yucatan, Mexico. A total of 260 lateral cephalograms of patients between 18 and 59 years of age were digitally traced using the Ricketts and Björk-Jarabak cephalometric analyses to determine the direction of facial growth and facial biotype using Dolphin Imagine software. Cohen's kappa statistical test was performed to establish the strength of agreement between the diagnostic results obtained by the cephalometric analyses. A poor diagnostic concordance strength was found for growth direction (K=0.105), and acceptable for facial biotype (K=0.362). The concordance strengths for each diagnostic possibility (level) ranged from slight to acceptable, except for the brachyfacial and dolichofacial biotypes, with a moderate strength of agreement. In conclusion, the Ricketts and Björk-Jarabak cephalometric measurements used for the determination of facial biotype and facial growth direction could suggest non-concordant diagnostic assessments in some individuals.